IMPLEMENTASI OTONOMI DAERAH TERHADAP EFEKTIVITAS PELAYANAN PUBLIK PADA PENYELENGGARAAN PEMERINTAHAN DESA DI DESA SANDIK - Muhamad Zaki; M Adli Rafif; Khairul Imam; Janeva Haerani; Latifatul Husna; Nila Widiya Wati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effectiveness of regional autonomy implementation in village governance in relation to public service delivery in Sandik Village, Batulayar Subdistrict, West Lombok Regency. Regional autonomy grants the village authority to manage governance and public services that align with the needs of the local community. Sandik Village has implemented various public service programs, including administrative, health, education, literacy, and socio-economic development services, with the goal of improving community welfare. The research method used is qualitative, with data collected through interviews, observations, and documentation. The results show that the implementation of regional autonomy has had a positive impact on the quality of public services in various sectors, particularly in access to health and education. Additionally, the people of Sandik Village are able to participate in policy-making and oversight of village government performance. Regional autonomy implementation also allows village officials to take on greater responsibility in managing the village budget in a transparent and accountable manner. This study is expected to contribute to more effective policy formulation and raise public awareness to actively participate in village governance.